Interdisciplinary Science - Science of the Invisible - Student Document - Harrison, Tim; Ryder, Karl; Woodward, Jonathan; Evans Cory; Raine, Derek; Davies, Dai; Ellis, Andrew; Williams, Dylan (The University of Hull)
In Science of the Invisible you will explore the structure of microscopic objects from cells to molecules to atoms. At the smallest scale the world is governed by quantum mechanics which controls the properties of atoms and their binding to form molecules. You will also learn about the states of matter, gases liquids and solids, and how their properties arise from the properties of their constituents.